Networked Cooperation: How the European Union Mobilizes Peacekeeping Forces to Project Power Abroad. (20th October 2019) - Henke, Marina E.
Abstract: How does the European Union (EU) recruit troops and police to serve in EU peacekeeping missions? This article suggests that pivotal EU member states and EU officials make strategic use of the social and institutional networks within which they are embedded to bargain reluctant states into providing these forces. These networks offer information on deployment preferences, facilitate side-payments and issue-linkages, and provide for credible commitments. EU operations are consequently not necessarily dependent on intra-EU preference convergence—as is often suggested in the existing literature. Rather, EU force recruitment hinges on highly proactive EU actors, which use social and institutional ties to negotiate fellow states into serving in an EU missions.